STANDARDIZATION IN FOREIGN COUNTRIES - Davlyatova Mavlyuda Bakhtiyorovna; Shernazarova Dilnoza Shuxratovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
In recent years, the role of accurate and reliable measurements in all types of society's activities has sharply increased, measuring technology is constantly being improved, accreditation systems for testing and calibration laboratories are developing, etc. skills in the use of measuring instruments [1-13]. Standardization is the activity of establishing rules and characteristics for the purpose of their voluntary and reusable use, aimed at achieving order in the areas of production and circulation of products and increasing the competitiveness of products, works and services [11].